2011
DOI: 10.1007/s10900-011-9444-9
|View full text |Cite
|
Sign up to set email alerts
|

Hookah Use Among College Students from a Midwest University

Abstract: National data indicate nearly a quarter of college students smoked from a hookah at some point in their lifetime regardless of gender. To address this issue, researchers assessed the perceptions, knowledge, beliefs of hookah users at a large Midwestern University and also determined what other drug related high-risk behaviors were associated with this behavior. An anonymous, online survey was sent to 2,000 randomly selected undergraduate students from a large Midwestern University. Researchers used a cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 16 publications
(29 reference statements)
7
86
1
2
Order By: Relevance
“…In the present study, the percentage of males smoking hookah was more compared to females; same trend was observed in earlier studies (Mazaik et al, 2004;Poyrazoglu et al, 2010;AL-Naggar and Saghir Fatma, 2011). While higher percentage of female hookah smokers has been reported in Jordon (DarOdeh et al, 2010), no gender difference was observed in studies from US (Braun et al, 2012;Brockman et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, the percentage of males smoking hookah was more compared to females; same trend was observed in earlier studies (Mazaik et al, 2004;Poyrazoglu et al, 2010;AL-Naggar and Saghir Fatma, 2011). While higher percentage of female hookah smokers has been reported in Jordon (DarOdeh et al, 2010), no gender difference was observed in studies from US (Braun et al, 2012;Brockman et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…39.21% Pune youth smoked for relaxation as versus 25% smokers in US who also reported that hookah smoking was a part of socializing, and was greatly influenced by the peers (Braun et al, 2012). Usually, hookah smoking is enjoyed in the company of friends (Maziak et al, 2004) and thus has become a group socializing activity (Aljarrah et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings corroborate past studies that indicate hookah smoking is increasingly popular among young adults, especially those who have or are working towards obtaining a college degree. 36,40,43,44 There are currently many hookah establishments that have emerged and these locations tend to be in "trendy" locations such as cafes and lounges in metropolitan areas that are often located near college campuses. Our findings might be related to the strategic locations of hookah establishments near and/or around college campuses, or perhaps they are due to the social networking and marketing of hookah use that is clustered among college students.…”
Section: Discussionmentioning
confidence: 99%